2023
DOI: 10.3390/v15020359
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible Gastroenteritis Virus: An Update Review and Perspective

Abstract: Transmissible gastroenteritis virus (TGEV) is a member of the alphacoronavirus genus, which has caused huge threats and losses to pig husbandry with a 100% mortality in infected piglets. TGEV is observed to be recombining and evolving unstoppably in recent years, with some of these recombinant strains spreading across species, which makes the detection and prevention of TGEV more complex. This paper reviews and discusses the basic biological properties of TGEV, factors affecting virulence, viral receptors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 175 publications
0
5
0
Order By: Relevance
“…Notably, the sensitivity (94.4%) and specificity (92.6%) of the COE-iELISA are significantly higher than that of the indirect ELISA established by Liu et al (sensitivity and specificity of 92.6 and 90.1%) [40]. With the continuous development of vaccines in recent years, the prevalence of TGEV and its variant PRCV in diarrhea pigs in China is very low [41], and the detection rate in clinical samples is approximately <3% [42], making it less easy to obtain positive serum samples. A previous study tested a total of 2987 clinical samples from five provinces in southern China from 2012 to 2018, and the results indicated that the rate of mono-infection of TGEV in samples tested was just 0.33% (10/2987) [43].…”
Section: Discussionmentioning
confidence: 89%
“…Notably, the sensitivity (94.4%) and specificity (92.6%) of the COE-iELISA are significantly higher than that of the indirect ELISA established by Liu et al (sensitivity and specificity of 92.6 and 90.1%) [40]. With the continuous development of vaccines in recent years, the prevalence of TGEV and its variant PRCV in diarrhea pigs in China is very low [41], and the detection rate in clinical samples is approximately <3% [42], making it less easy to obtain positive serum samples. A previous study tested a total of 2987 clinical samples from five provinces in southern China from 2012 to 2018, and the results indicated that the rate of mono-infection of TGEV in samples tested was just 0.33% (10/2987) [43].…”
Section: Discussionmentioning
confidence: 89%
“…Much like their human counterparts, animal CoVs have a genome consisting of a linear, positive-sense, single-stranded RNA of approximately 22,000 to 36,000 nucleotides, with a 5′-cap structure and a 3′-polyadenylated tail [ 115 ]. They have a genome structure that comprises two open reading frames (ORFs) located in the 5′-proximal two-thirds of the genome [ 35 , 38 , 116 ]. These ORFs, known as ORF1a and ORF1b, encode the replicase polyproteins pp1a and pp1ab [ 117 ], as shown in Figure 3 .…”
Section: Genomic Structure Of Animal Covs and Function Of Their Relat...mentioning
confidence: 99%
“…Another member of the alphacoronavirus subfamily, closely related to PEDV, is TGEV. It is one of the major infectious agents responsible for the enteritis and severe diarrhea observed in swine, with its mortality rates reaching 100% in the piglet population [78]. As a coronavirus, it contains a single-stranded genomic RNA with a size of 28.5 Kb approximately, encoding sixteen NSPs, four structural (S, M, N, and E), and three accessory (ORF3a, ORF3b, and ORF7) proteins [79].…”
Section: Transmissible Gastroenteritis Virus (Tgev)mentioning
confidence: 99%